Pregabalin abuse for enhancing sexual performance: case discussion and literature review. (27th August 2014) - Osman, M.; Casey, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Pregabalin is a γ-aminobutyric acid analogue that is primarily prescribed in psychiatry for management of generalized anxiety disorder. The belief in its low potential for abuse has placed it in a superior position to other anxiolytic agents. However, more recent, concerns have been raised about the addictive potential of pregabalin. This problem has not received much attention nor has the mechanism of its development. There is also a lack of understanding of the difference in the experience of abusing pregabalin in contrast to abusing other illicit drugs. We report the case of a 55-year-old patient with a background history of multiple psychoactive substances misuse who elaborated on his own personal experience of pregabalin abuse. He consumed a month's supply of this medication over 2 days and realized an enhancement in sexual desire and excitement. This effect should be considered when prescribing pregabalin.